**Weight - Buoyancy = (mass x Gravity) - Buoyancy**

**Since the net acceleration is g/6 upwards, then we have:**

**a = -g/6; **

**we also know that a = F / m.**

**[Note this is a -ve sign because the acceleration is in the opposite direction to gravity]**

**so: **

**a = -g/6 = [(m x g) - B] / m**

**Solving for B:-**

**g/6 = mg/m - B/m**

**B/m = g + g/6**

**B = gm [1 + 1/6]**

**B = 7/6 x gm**

**After the sand is added in the new mass is (m + ms) and a = g/6.**

**Net Force = weight of box + weight of sand - Buoyancy**

**Net Force = m x g + ms x g - B**

**B = 7/6 x gm**

**So Net force = mg + ms x g - 7/6 x gm = ms x g - gm/6= g [ ms - m/6]**

**Force = mass x acceleration. **

**Now mass total is m + ms and acceleration is g/6**

**So g [ ms - m/6] = F = (m+ms)x a**

**g [ms - m/6] = (m + ms) x g/6ms - m/6 = (m + ms) 1/6ms - 1/6 ms = m/6 + m/65/6 ms = 2m/65 ms = 2mms = 2m/5**

**Hence, the mass = 2 x 5/5 = 2**